Forensic medical evaluation of fatal cases of gastrointestinal diseases as a marker of the quality of surgical care for children in Ukraine - А.М. Biliakov; B.V. Mikhailychenko; Ye.O. Rudenko (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Forensic medical assessment of the quality of medical care is a critically important task for improving the healthcare sector. Surgical practice is associated with high risks to the lives of patients, as it combines the stage of planning surgical intervention, its direct implementation with the involvement of an anesthesiologist, the postoperative period and subsequent recovery. Diseases that primarily require surgical intervention and the lack of treatment of which can lead to death are pathologies of the gastrointestinal tract. At the same time, the health of the nation is determined by the level of health of children and adolescents, because this is the basis of economic and social life and development of the state as a whole. Analysis of fatal cases of deaths from diseases of the gastrointestinal tract is an indirect marker of the quality of surgical medical care for children.